(untitled) (Teacher Half-Yearly Journal, 2025)
This study investigates the association between the education and occupation of household heads and household financing for basic education in Nepal. Utilizing a quantitative approach with a correlational and descriptive design, data was collected through structured questionnaires from 380 households in Ratuwamai Municipality of Morang district. The findings reveal significant differences in per-child household financing for basic education based on the occupation and education levels of household heads. Higher-paying professions and higher parental education levels are associated with greater household financial resources allocated to children’s education. Conversely, households with low-income occupations and lower parental education levels face financial barriers, resulting in reduced prioritization of education. These findings underscore the association of socioeconomic factors on household financing decisions and highlight the importance of considering household head occupation and parental education in household financing on basic education.